Functional food-related bioactive compounds: effect of sorghum phenolics on cancer cells in vivo and conversion of short- to long-chain omega-3 polyunsaturated fatty acids in duck liver in vivo - Chen, Xi (Kansas State University, 2017)
Many functional food related bioactive compounds have been discovered and draw the attention of scientists. This dissertation focused on sorghum phenolic compounds and omega-3 polyunsaturated fatty acids. Study 1: phenolic agents in plant foods have been associated with chronic disease prevention, especially cancer. However, a direct evidence and the underlying mechanisms are mostly unknown. This study selected 13 sorghum accessions and was aim to investigate: (1) the effect of extracted sorghum phenolics on inhibiting cancer cell growth using hepatocarcinoma HepG2 and colorectal adenocarcinoma Caco-2 cell lines; (2) and the underlying mechanisms regarding cytotoxicity, cell cycle interruption, and apoptosis induction. Treatment of HepG2 and Caco-2 cells with the extracted phenolics at 0-200 M GAE (Gallic acid equivalent) up to 72 hrs resulted in a dose- and time-dependent reduction in cell number. The underlying mechanism of cell growth inhibition was examined by flow cytometry, significant inverse correlations were observed between the decreased cell number and increased cell cycle arrest at G2/M or induced apoptosis cells in both HepG2 and Caco-2 cells. The cytotoxic assay showed that the sorghum phenolic extracts were non-toxic. Although it was less sensitive, a similar inhibitory impact and underlying mechanisms were found in Caco-2 cells. These results indicated for the 1st time that a direct inhibition of either HepG2 or Caco-2 cell growth by phenolic extracts from13 selected sorghum accessions was due to cytostatic and apoptotic but not cytotoxic mechanisms. In addition, these findings suggested that sorghum be a valuable functional food by providing sustainable phenolics for potential cancer prevention. Study 2: omega-3 polyunsaturated fatty acids (ω-3 PUFAs) especially long-chain ω-3 PUFAs, have been associated with potential health benefits in chronic disease prevention. However, the conversion rate from short- to long-chain ω-3 PUFAs is limited in human body. This study was aim to assess the modification of fatty acid profiles as well as investigate the conversion of short- to long-chain ω-3 PUFAs in the liver of Shan Partridge duck after feeding various dietary fats. The experimental diets substituted the basal diet by 2% of flaxseed oil, rapeseed oil, beef tallow, or fish oil, respectively. As expected, the total ω-3 fatty acids and the ratio of total ω-3/ ω-6 significantly increased in both flaxseed and fish oil groups when compared with the control diet. No significant change of total saturated fatty acids or ω-3 fatty acids was found in both rapeseed and beef tallow groups. Short-chain ω-3 α-linolenic acid (ALA) in flaxseed oil-fed group was efficiently converted to long-chain ω-3 docosahexaenoic acid (DHA) in the duck liver. This study showed the fatty acid profiling in the duck liver after various dietary fat consumption, provided insight into a dose response change of ω-3 fatty acids, indicated an efficient conversion of short- to long-chain ω-3 fatty acid, and suggested alternative long-chain ω-3 fatty acid-enriched duck products for human health benefits. In conclusion, the two studies in this dissertation provided a fundamental understanding of anti-cancer activity by sorghum phenolic extracts and the conversion of short- to long-chain ω-3 PUFAs in duck liver, contribute to a long term goal of promoting sorghum and duck as sustainable phenolic and ω-3 PUFAs sources as well as healthy food products for human beings.
Keywords: Functional food; Sorghum; Phenolics; Omega-3 fatty acids